Collaboration within the global vaccine safety surveillance ecosystem during the COVID-19 pandemic: lessons learnt and key recommendations from the COVAX Vaccine Safety Working Group - Rebecca E Chandler; James Milligan; Emmanuelle Espie; Katharina Hartmann; Madhava Ram Balakrishnan; Daniel Brasseur; Philip Bryan; Corinne Jouquelet-Royer; Linda Nesbitt; Shanthi Pal; Alexander Precioso; Paulo Takey; et al. (BMJ Global Health)
This analysis describes the successes, challenges and opportunities to improve global vaccine safety surveillance as observed by the Vaccine Safety Working Group from its role as a platform of exchange for stakeholders responsible for monitoring the safety of vaccines distributed through the COVAX mechanism. Three key elements considered to be essential for ongoing and future pandemic preparedness for vaccine developers in their interaction with other members of the vaccine safety ecosystem are (1) the availability of infrastructure and capacity for active vaccine safety surveillance in low-income and middle-income countries (LMICs), including the advancement of concepts of safety surveillance and risk management to vaccine developers and manufacturers from LMICs; (2) more comprehensive mechanisms to ensure timely exchange of vaccine safety data and/or knowledge gaps between public health authorities and vaccine developers and manufacturers; and (3) further implementation of the concept of regulatory reliance in pharmacovigilance. These aims would both conserve valuable resources and allow for more equitable access to vaccine safety information and for benefit/risk decision-making.